Precision of CT-based micromotion analysis is comparable to radiostereometry for early migration measurements in cemented acetabular cups - Brodén, Cyrus; Sandberg, Olof; Olivecrona, Henrik; Emery, Roger; Sköldenberg, Olof (Acta Orthopaedica, 2021)
Background and purpose — CT (computed tomography) based methods have lately been considered an alternative to radiostereometry (RSA) for assessing early implant migration. However, no study has directly compared the 2 methods in a clinical setting. We estimated the precision and effective radiation dose of a CT-based method and compared it with marker-based RSA in 10 patients with hip arthroplasty. Patients and methods — We included 10 patients who underwent total hip replacement with a cemented cup. CT and RSA double examinations were performed postoperatively, and precision and effective dose data were compared. The CT data was analyzed with CT micromotion analysis (CTMA) software both with and without the use of bone markers. The RSA images were analyzed with RSA software with the use of bone markers. Results — The precision of CTMA with bone markers was 0.10–0.16 mm in translation and 0.31°–0.37° in rotation. Without bone markers, the precision of CTMA was 0.10–0.16 mm in translation and 0.21°–0.31° in rotation. In comparison, the precision of RSA was 0.09–0.26 mm and 0.43°–1.69°. The mean CTMA and RSA effective dose was estimated at 0.2 mSv and 0.04 mSv, respectively. Interpretation — CTMA, with and without the use of bone markers, had a comparable precision to RSA. CT radiation doses were slightly higher than RSA doses but still at a considerably low effective dose.